Comparative analysis of algorithms for projected laser line identification and recognition for 3d scanning devices - Andrushchak, N.; Vasylyshyn, В.; Chornenkyy, V. (Видавництво Львівської політехніки, 2015)
Проведено порівняльний аналіз алгоритмів визначення та розпізнавання лінії лазерного випромінювання, описано принцип дії, негативні і позитивні сторони кожного методу, а також показано можливості їхнього застосування для пристроїв 3D-сканування. Тестування алгоритмів проведено на експериментальній установці з використанням засобів С++ і бібліотеки OpenCV. Показано, що залежно від розмірів зображення та деталізації вхідного зображення слід рекомендувати той чи інший алгоритм. This paper is devoted to the comparative analysis of algorithms for identification and recognition of the projected laser line. The principles of these methods, their negative and positive aspects and the possibilities of their implementation for 3D-scanning devices are described. Algorithms approbation was conducted on experimental setup using C++ programming language and OpenCV library. It is shown that, depending on the image size and details of the input image, one or another algorithm should be applied.
Keywords: медіанний метод; метод середніх квадратів; апроксимація; 3D-сканер; median method; least square method; approximation; 3D-scanner